Lifespan benefits for the combination of rapamycin plus acarbose and for captopril in genetically heterogeneous mice. Issue 12 (30th September 2022) - Strong, Randy; Miller, Richard A.; Cheng, Catherine J.; Nelson, James F.; Gelfond, Jonathan; Allani, Shailaja Kesaraju; Diaz, Vivian; Dorigatti, Angela Olsen; Dorigatti, Jonathan; Fernandez, Elizabeth; Galecki, Andrzej; Ginsburg, Brett; et al.
Abstract: Mice bred in 2017 and entered into the C2017 cohort were tested for possible lifespan benefits of (R/S)‐1, 3‐butanediol (BD), captopril (Capt), leucine (Leu), the Nrf2‐activating botanical mixture PB125, sulindac, syringaresinol, or the combination of rapamycin and acarbose started at 9 or 16 months of age (RaAc9, RaAc16). In male mice, the combination of Rapa and Aca started at 9 months and led to a longer lifespan than in either of the two prior cohorts of mice treated with Rapa only, suggesting that this drug combination was more potent than either of its components used alone. In females, lifespan in mice receiving both drugs was neither higher nor lower than that seen previously in Rapa only, perhaps reflecting the limited survival benefits seen in prior cohorts of females receiving Aca alone. Capt led to a significant, though small (4% or 5%), increase in female lifespan. Capt also showed some possible benefits in male mice, but the interpretation was complicated by the unusually low survival of controls at one of the three test sites. BD seemed to produce a small (2%) increase in females, but only if the analysis included data from the site with unusually short‐lived controls. None of the other 4 tested agents led to any lifespan benefit. The C2017 ITP dataset shows that combinations of anti‐aging drugs may have effects that surpass the benefits produced by either drug used alone, and that additional studies of captopril, over a wider range of doses, are likely to be rewarding. Abstract : The C2017 ITP dataset shows that combinations of anti‐aging drugs may have effects that surpass the benefits produced by either drug used alone. The data further show that males benefit more than females from the combination of RAPA and acarbose.